Influences of long-term CAPD on cardiac function - Ohta, Makoto; Kameda, Chikako; Mizuguchi, Masato; Sato, Shigeaki; Tanaka, Hiroshi; Takamizawa, Shigetaka; Sugimoto, Ken-ichi; Miyahara, Tadashi; Kawaguchi, Yoshindo; Ohmura, Nobuhiro (Journal of Japanese Society for Dialysis Therapy, 1989)
To explore the influences of CAPD on cardiac function, hemodynamic changes were evaluated by ultrasonic echocardiography (UCG) in patients with chronic renal failure undergoing long-term CAPD. The subjects consisted of 10 patients who had been on CAPD for at least 3 years. Left ventricular diastolic dimension (LVDd), left ventricular systolic dimension (LVDs), intraventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT), E-point septal separation (EPSS), and inferior vena cava dimension (IVCD) were measured by UCG, and the following parameters were calculated: cardiac index (CI), stroke volume (SV), ejection fraction (EF), fractional shortening (FS). These parameters were measured on two separate occasions, one shortly after the initiation of CAPD (less than 2 months, Stage 1) and the other 3 years after regular CAPD (Stage 2). In the latter stage, a vector electrocardiograph (VCG) and electrocardiograph (ECD) were also recorded before and after drainage of the dialysis fluid. The following observations were made: (1) Instillation of the dialysis fluid did not affect any of the parameters except for IVCD, which was slightly decreased at both Stage 1 and 2; (2) IVST and LVPWT at Stage 2 were greater than at Stage 1. LVDs, LVDd, SV and CI were not significantly different from each other at Stage 1 and Stage 2. EF, FS and EPSS tended to improve after long-term CAPD. There was no significant change in IVCD upon comparison between Stage 1 and Stage 2; (3) The electrical axis of the heart was not changed by instillation of dialysis fluid, indicating no significant deviation of cardiac electrical position; (4) As compared with our previous study performed in patients under long-term hemodialysis (HD), CAPD had less influence on these parameters; (5) Deterioration of cardiac function was prevented by antihypeertensive treatment in patients with hypertension. in long-term CAPD. The present observations indicate that cardiac work did not increase, and that left ventricular contraction and compliance were well preserved in patients on long-term CAPD. It thus appears that CAPD is a favorable dialysis modality in terms of cardiac function, in comparison with HD.